Online Intergroup Polarization Across Political Fault Lines: An Integrative Review - Bliuc, Ana-Maria; Bouguettaya, Ayoub; Felise, Kallam D. (Frontiers in Psychology, 2021)
We revisit the construct of political polarization and current distinctions between issue-driven and affective polarization. Based on our review of recent research on polarization from psychology, political science, and communication, we propose to treat polarization as a process that integrates the concepts of social identification (collective self-definition) with ideologically opposed camps - that is, psychological groups based on support or opposition to specific socio-political issues and policies (related to issue-driven polarization), and that of ideological and psychological distancing between groups (related to affective polarization). Furthermore, we discuss the foundations of polarizing groups – and more specifically, the role of conflicting collective narratives about social reality in providing an initial platform for polarization in a technologically networked world. In particular, we highlight the importance of online media in facilitating and enhancing polarization between ideologically opposed camps. As a theoretical contribution, the review provides a more functional conceptualization of polarization that can explain how polarization may occur across partisan fault lines and in domains outside of politics. We conclude with a discussion of new pathways to the study of polarization which this integrative conceptualization opens.